Schiff's base of pyridyl substituted triazoles as new and effective corrosion inhibitors for mild steel in hydrochloric acid solution - Ansari K.R.; Quraishi M.A.; Singh A. (My University, 2025)
Three Schiff's bases namely (3-phenylallylidene) amino-5-(pyridine-4-yl)-4H-1,2,4-triazole-3-thiol (SB-1), 3-mercapto-5 (pyridine-4-yl)-4H-1,2,4-triazole-4-yl) imino) methyl) phenol (SB-2) and (4-nitrobenzylidene) amino)-5-(pyridine-4-yl)-4H-1,2,4-triazole-3-thiol (SB-3) were synthesized and investigated as corrosion inhibitors for mild steel (MS) in 1M HCl. SB-1 exhibited best inhibition performance (96.6 η%) at 150mgL-1. The studied inhibitors follow Langmuir adsorption isotherm. Potentiodynamic polarization data suggests mixed-mode of corrosion inhibition. The effect of molecular structure on inhibition efficiency was investigated by theoretical calculations using density function theory (DFT) methods. Surface analysis supports the formation of a protective inhibitor film on the mild steel surface. © 2013 Elsevier Ltd.